2022
DOI: 10.3390/plants11101295
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Anti-Proliferative, and Kinase Inhibitory Activity of Phenanthroindolizidine Alkaloids Isolated from Tylophora indica

Abstract: The phenanthroindolizidine alkaloid (-)-tylophorine has been reported for its significant anticancer activity working through different biomechanistic pathways. The current study aimed to evaluate the anticancer activity of phenanthroindolizidine alkaloids isolated from Tylophora indica. Six phenanthroindolizidine alkaloid (compounds 1–6) in addition to septicine (7), chlorogenic acid (8), and chlorogenic acid methyl ester (9) were isolated from Tylophora indica using different chromatographic techniques inclu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…Nevertheless, in silico docking studies postulate kinase inhibition through binding to the ATP-binding site as a pharmacological mode of action for PAs. Studies by Liu et al report the blocking of AKT for another epimer of compound ( 1 ), namely HTBP1 [ 87 ], and Mostafa et al showed blocking of Aurora A and B kinases for tylophorinine and for ( 2 ) [ 89 ]. However, to date, the function of kinase inhibition by PAs is unclear for breast cancer.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, in silico docking studies postulate kinase inhibition through binding to the ATP-binding site as a pharmacological mode of action for PAs. Studies by Liu et al report the blocking of AKT for another epimer of compound ( 1 ), namely HTBP1 [ 87 ], and Mostafa et al showed blocking of Aurora A and B kinases for tylophorinine and for ( 2 ) [ 89 ]. However, to date, the function of kinase inhibition by PAs is unclear for breast cancer.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, proliferation blocking by PAs might rely on inhibiting checkpoint proteins in the cell cycle or by inhibiting DNA replication. Recently, Aurora A and B kinases were found as novel targets for tylophorinine and for ( 2 ) at a low micromolar concentration in MCF7 [ 89 ]. As a direct substrate, p53 is phosphorylated and subsequently degraded [ 95 ].…”
Section: Discussionmentioning
confidence: 99%
“…Merr, an Indian native species, was described by Mostafa et al (2022). The compound presented IC 50 values of 6.45, 4.77, and 20.08 µM in MCF-7, HepG2, and HCT-116 cell lines, respectively [12]. The in vitro cytotoxic and anti-migratory effects of extracts from Marantodes pumilum Blume Kuntze, a Malaysian plant, as well as of an isolated compound from the chloroform fraction, 5-henicosene-1-yl-resorcinol, on prostate cancer cells (PC3) was shown by Hanafi et al (2023).…”
mentioning
confidence: 97%